(3cJGH GdUdhGJs - (3GdeXaQs
(3ChdgG (B:s
(3GdebUO GdKGdK ai HGbi GdUdhGJ hajg NeSI aUhd GdChd ajg UdGI GdLeYI s
(3BNQgG (B:s
(3jSJOd dPdc HGWdGb GdLeGYI ai NjQi GHf GdeZjQI hGHf CHj bQI dh de fbd HGf GdfXQ ajgeG s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdchaI (B- (3HZOGO (B(2) s
Keywords: (3Yde GdaQGFVs